2020
DOI: 10.1037/bul0000221
|View full text |Cite
|
Sign up to set email alerts
|

Aftereffects and deactivation of completed prospective memory intentions: A systematic review.

Abstract: Prospective memory, the ability to perform an intended action in the future, is an essential aspect of goal-directed behavior. Intentions influence our behavior and shape the way we process and interact with our environment. One important question for research on prospective memory and goal-directed behavior is whether this influence stops after the intention has been completed successfully. Are intention representations deactivated from memory after their completion, and if so, how? Here, we systematically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 120 publications
1
16
0
1
Order By: Relevance
“…The target of regulation corresponds to the subject of meta-control, i.e., the set of control processes being monitored and regulated. For instance, in the Stroop task, participants may invoke meta-control to regulate the amount of proactive engagement in a control-dependent behavior (Bustamante et al, 2021;Dey & Bugg, 2021;Lieder & Iwama, 2021), whereas in a prospective memory task, meta-control is needed to regulate the trade-off between the requirement to shield a current task-goal from interfering stimuli and the requirement to monitor the environment for cues signaling that one should switch to a different task (Goschke & Dreisbach, 2008;Möschl et al, 2020). However, meta-control also may regulate more complex control policies that determine exploratory versus exploitative behavior (Marković et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The target of regulation corresponds to the subject of meta-control, i.e., the set of control processes being monitored and regulated. For instance, in the Stroop task, participants may invoke meta-control to regulate the amount of proactive engagement in a control-dependent behavior (Bustamante et al, 2021;Dey & Bugg, 2021;Lieder & Iwama, 2021), whereas in a prospective memory task, meta-control is needed to regulate the trade-off between the requirement to shield a current task-goal from interfering stimuli and the requirement to monitor the environment for cues signaling that one should switch to a different task (Goschke & Dreisbach, 2008;Möschl et al, 2020). However, meta-control also may regulate more complex control policies that determine exploratory versus exploitative behavior (Marković et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This deactivation of completed intentions is considered to be essential for goal-directed behavior, given that it enables focusing on new task demands and might prevent perseverative behavior (Goschke & Bolte, 2018;Mayr & Keele, 2000). Previous studies, however, showed that completed intentions can interfere with subsequent tasks in terms of aftereffects of completed intentions (Möschl et al, 2020). What are the mechanisms behind such aftereffects, and what causes us to slow down our ongoing-task performance while pursuing an intention in the first place?…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, PM research investigated the deactivation of completed intentions within event-based PM paradigms with no-longer-relevant PM cues (Anderson & Einstein, 2017 ; Bugg et al, 2013 ; Bugg et al, 2016 ; Möschl et al, 2020 ; Walser et al, 2012 ; Walser et al, 2017 ). In these paradigms, participants first perform an event-based PM task, in which they are instructed to perform a particular action (PM response, e.g., press spacebar) once they notice a specific PM cue that signals an opportunity to retrieve and execute the intended action (e.g., a specific symbol).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A PM commission error is the act of erroneously repeating a PM intention when it is no longer relevant (e.g., erroneously taking medication that is no longer appropriate to take). Examining the underlying mechanisms that cause commission errors is crucial to understanding why they happen and how to prevent them from occurring (see Möschl et al, 2020 , for a recent review).…”
mentioning
confidence: 99%